Citometria de fase sólida aplicada ao teste de esterilidade do produto Cloreto de Sódio 0,9% Solução Injetável - Silva, Gisele Badauy Lauria (2015)
The sterility test is a test that certificate the absence of viable microorganisms in pharmaceutical raw materials, drugs and medical device. The Solid Phase Cytometry method (SFC) is based on the detection of viable cells through the use of viability markers reagents, that permeate the cell membrane and are cleaved by nonspecific esterase enzymes, forming the fluorochromes that are detected by ChemScan RDI® equipment. It is a fast and innovative method for the sterile injecting drugs area. The objective of the study was to evaluate and validate this technology applied to the sterility test, of the product Sodium Chloride (NaCl) 0.9% Injectable Solution, using the ChemScan RDI® equipment (CS RDI®). Eight microorganisms were evaluated, being six compendial (Clostridium sporogenes NCTC 12935 (ATCC 11437), Pseudomonas aeruginosa NCTC 12924 (ATCC 9027), Staphylococcus aureus NCTC 10788 (ATCC 6538), Bacillus subtilis NCTC 10400 (ATCC 6633), Aspergillus brasiliensis NCPF 2275 (ATCC 16404) and Candida albicans NCPF 3179 (ATCC 10231)) and two "in house” microorganisms, obtained from bioburden monitoring of pre sterilization (Micrococcus luteus and Staphylococcus epidermidis). The Solid Phase Cytometry methodology through logistic regression statistical analysis and Chi-square test, showed to be more rapid than the sterility test by membrane filtration (MF) for all tested microorganisms, reducing the analysis time from 14 days to about 3 hours. The method was validated by the use of qualitative parameters: specificity, limit of detection and robustness.